Hyperbaric oxygen prevents bacterial translocation in thermally injured rats - GÜLLÜOĞLU, MAHMUT BAHADIR (TAYLOR & FRANCIS INC, 2002)
This study was designed to evaluate the effects of hyperbaric oxygen (HBO2) on intestinal microflora and bacterial translocation (BT) caused by experimentally induced thermal injury in rats. Rats were separated into four groups, namely, HBO2 group, thermal injury (TI) group, TI + HBO2 group, and control group. All groups were further separated into short-term (2 days) and long-term (7 days) treatment or injury groups. Control group was neither exposed to thermal injury nor was given any treatment. Thirty percent second-degree thermal burn was induced on the dorsal body part of the rats in TI groups. In the HBO2 groups, rats received HBO2 treatment either without TI or following TI induction, for 2 and 7 days, respectively. Sampling from tissues and portal vein was performed on day 3 in the short-term groups and on day 8 in the long-term groups. Samples were cultured for identification of bacteria and colony counts. HBO2 treatment significantly reduced the colony counts of endogenous microflora in distal ileum of healthy rats (p < .05), while TI significantly increased the colony counts of endogenous microflora in distal ileum in short- and long-term TI groups (p < .05). Presence of bacterial translocation was proven by bacterial isolation in mesenteric lymph nodes, liver, spleen and blood. Both short- and long-term HBO2 treatment following TI significantly reduced the colony counts of intestinal microflora (p < .05) and prevented bacterial translocation almost completely. It is concluded that thermal injury causes both bacterial overgrowth within intestinal lumen and bacterial translocation across the intestinal wall. HBO2 administration prevents both bacterial overgrowth and translocation.
Keywords: bacterial translocation; burn; hyperbaric oxygen; thermal injury; BURN; HYPEROXIA; THERAPY; SEPSIS; PSEUDOMONAS; FAILURE